Compensation effects in a Socially Responsible Investment context - Woegerbauer, Barbara (2019)
A central idea of Socially Responsible Investing (SRI) is that investors accept a loss in financial returns if they are compensated by non-financial utility that they derive from their sustainable investment. This study investigates the idea of financial penalty in SRI by examining return and risk patterns of more vs. less sustainable assets in Europe, Japan and the United States. The four distinct ESG scores provided by Bloomberg (ESG composite score, environmental, social, governance sub-scores) are used in this thesis to proxy sustainability. Responsible and irresponsible portfolios are built by grouping assets based on their scores. Portfolios are constructed separately for the 4 distinct ESG dimensions and for 3 geographies. The resulting 12 investment segments are analyzed to make a statement between a potential financial penalty in the sense of a suboptimal return and risk profile. This study finds that, in most investment segments, there is nothing to be lost from investing in the responsible portfolios compared to investing in the irresponsible portfolios, but that ESG-rated assets tend to outperform the market in general. It follows the notion of compensation effects in this specific approach is widely misleading and it appears that investing good simultaneously means investing really well.